Formation of the idea of neoliberalism in the sphere of higher education in the USA - Amandykova, S.K.; Altynbasov, B.O. (Bulletin of the Karaganda University “Law Series”, 2021)
This article presents a theoretical analysis, the historical development of higher education and the formation of the idea of neoliberalism in the field of higher education in the United States of America. Analyzing higher education system in the USA from a historical point of view, the authors of the article tried to comprehensively study each stages of the historical development of higher education and the impact of globalization on the emergence of neoliberal ideas in the field of higher education. Various scientific and philosophical thoughts regarding the management system in the field of higher education are illustrated. In particular, various management systems of higher educational institutions in the United States of America were examined. Considering that the study of the management system is one of the main goals of the work, the authors analyzed how the USA experience will be reflected in the Kazakh conditions. The effective practice of the world's leading countries in the formation of the idea of neoliberalism was considered. The main factors influencing on the formation of the idea of neoliberalism, such as higher education, were identified, and actual problems of national higher education and science were highlighted, namely: issues of national higher education in the period of globalization and integration; issues of formation and development of a foreign language, scientific personnel at universities and research institutes. In addition, this article are the problems of applying the USA experience in the conditions of the Republic of Kazakhstan discussed. The article presents evidence-based recommendations for improving the national science of the Republic of Kazakhstan and developing the idea of neoliberalism as a factor of competitiveness of the Republic of Kazakhstan.